Pengaruh Penggunaan Model Pembeljaran Make a Match dan Team Games Tournament Terhadap Hasil Belajar IPAS Kelas V SDN 104206 Sei Rotan - Tinambunan, Fadjri Lewaldi; Gultom, Ibrahim; Simanjuntak, Eva Betty; Perangin-Angin, Laurensia Masri; Sirait, Albert Pauli (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the effect of the Make A Match and Team Games Tournament learning models on student learning outcomes in Natural and Social Sciences (IPAS) in class V SDN 104206 Sei Rotan for the 2024/2025 academic year. This study employs a quasi-experimental design with a two-group pretest-posttest design. The subjects of the research are two experimental classes, each consisting of 20 students. Class V-A uses the Make A Match model, while class V-B uses the Team Games Tournament model. The data collection instrument is a validated multiple-choice test that has been tested for reliability. The results of the study indicate a significant improvement in learning outcomes after the implementation of both learning models. The average posttest score for students in the Make A Match class is 81.25, an increase from the pretest score of 63. Meanwhile, the average post-test score for the Team Games Tournament class is 66.15, an increase from the pre-test score of 51. The t-test shows a significance value of 0.001 < 0.05, which means there is a significant difference between the two models. Thus, it can be concluded that both learning models have a positive effect on the learning outcomes of IPAS, but the Make a Match model has a more significant impact compared to the Team Games Tournament